Dual BRCA1 and BRCA2 pathogenic variants in an adolescent with syndromic intellectual disability. Issue 8 (8th August 2022) - Algouneh, Arash; Caudle, Michelle; Balci, Tugce; Andrade, Andrea; Penava, Debbie; Saleh, Maha
Abstract: Pathogenic variants in the BRCA1 and BRCA2 genes are associated with increased risk for breast and ovarian cancers. Concurrent mutations in both genes in the same individual are rare but pose specific challenges when identified, usually through multigene panel testing or infrequently from a genome‐wide analysis, such as whole‐exome sequencing (WES). We present a 15‐year‐old female patient with syndromic intellectual disability whose exome reanalysis identified secondary findings of pathogenic BRCA1 and BRCA2 variants, both inherited paternally. We discuss the significant challenges posed by this finding in genetic counseling and cancer risk management of an adolescent with nonverbal intellectual disability, as well as the impact on their family. This rare case highlights the potential increased diagnostic yield of whole exome sequencing reanalysis and the consequences of secondary medically actionable results in a pediatric patient. Abstract : We discuss the challenges in genetic counseling and cancer risk management of an adolescent with nonverbal intellectual disability and concurrent BRCA1 and BRCA2 mutations. This rare case highlights the potential increased diagnostic yield of whole‐exome sequencing reanalysis and the consequences of secondary medically actionable results in a pediatric patient.